The Analysis Study of Diet and Lifestyle Interventions for Insulin Resistance Patients with Nonalcoholic Fatty Liver: A Comprehensive Systematic Review - Aprilia Indah Purnomo; Charles Sanjaya Seikka (International Medical Journal Corp. Ltd, 2025)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease globally, affecting 20–30% of adults in developed countries and rising to 75% in individuals with obesity and 50–75% in those with type 2 diabetes mellitus (T2DM). The disease ranges from simple steatosis to non-alcoholic steatohepatitis (NASH) and may progress to fibrosis, cirrhosis, and liver failure. Insulin resistance (IR) plays a central role in its progression. This review examines the effects of diet and lifestyle interventions on IR and liver function in NAFLD patients. Methods: A systematic review adhering to PRISMA 2020 guidelines was conducted. Studies from 2015 to 2025 focusing on dietary or lifestyle interventions in NAFLD patients were included. Outcomes assessed included changes in IR (via HOMA-IR) and liver function (ALT, AST, GGT). Results: Eight relevant studies were included. Dietary interventions, such as the Mediterranean diet and calorie restriction, along with physical exercise, showed significant improvements in IR and liver function. Combined interventions yielded better outcomes compared to single-modality approaches. Discussion: Dietary interventions (Mediterranean diet, low-fat diet) and exercise (aerobic and resistance) significantly impact IR and liver function. The findings highlight the importance of individualized, comprehensive lifestyle interventions for NAFLD management. Conclusion: This review shows the effectiveness of diet and lifestyle interventions in managing NAFLD through improvements in insulin sensitivity and liver health. Combined approaches should be prioritized to optimize patient outcomes and long-term adherence to treatment.